High prevalence of multiple drug resistant enteric bacteria: Evidence from a teaching hospital in Southwest Nigeria - Adeyemi Kayode; Pelumi Okunrounmu; Abiodun Olagbende; Oyeronke Adedokun; Abdul-Wasiu Hassan; Glory Atilola (Elsevier, 2020)
The development and evolution of antimicrobial resistance (AMR) in pathogens has been reported to be one of the major issues confronting the global health community. The aim of this study was to examine the period prevalence of antibiotic resistance, as well as the trends and patterns in sensitivity profile of enteric bacteria isolated from urine samples of patients with UTIs in a teaching Hospital in south west Nigeria. Urine samples were collected from 77 patients with UTIs from February 2017 to October 2018. Standard laboratory methods were used for urine sample culture and bacterial identification. The Kirby-Bauer disk diffusion method was used to evaluate antimicrobial sensitivity. Predominant enteric bacteria isolates were Escherichia coli (24, 39.3%), Salmonella species (12, 19.7%), Klebsiella species (4, 6.6%), Providencia species (6, 9.8%), Proteus species (8, 13.1%), Serratia species (2, 3.3%), Yersinia species (1, 1.6%) and Morganella species (4, 6.6%). A large proportion (90.2%) of isolates obtained were multi-drug resistant. High resistance in amoxycillin-clavulanate (98%), cefuroxime (92%), erythromycin (90%) and ceftazidime (84%) were recorded. These results emphasize the importance of continuous screening and surveillance programmes for detection of AMR in enteric bacteria of public health importance. Keywords: Antimicrobial resistance, Enterobacteriaceae, Nigeria, Sub-Saharan Africa, UTIs